Efektivitas Konseling Gestalt Teknik Kursi Kosong dalam Meningkatkan Penyesuaian Diri Siswi Boarding School - Aulia Rahma Dhani; Winda Ratnadillah; Rizki Rosalinda Siregar (CV. Lentera Literasi Indonesia, 2026)
Adjustment difficulties are issues that affect students’ ability to interact and respond effectively to the demands of the school environment. This study aims to improve the adjustment abilities of a boarding school student, referred to as JS, through a series of counseling interventions. The study employed a qualitative approach with a case study design involving one research participant. Data were collected through behavioral observations, several counseling sessions, and the administration of the Problem Checklist (Daftar Cek Masalah/DCM) to identify the specific issues experienced by the student. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings show that JS experienced adjustment difficulties characterized by hesitation in expressing opinions, susceptibility to peer pressure, and a tendency to suppress emotions. After receiving the intervention, including the application of the Empty Chair technique, JS demonstrated positive changes, such as increased confidence in expressing feelings, improved ability to set personal boundaries, and more adaptive social responses. These results indicate that the Empty Chair technique can serve as an effective intervention option for students who experience challenges in personal and social adjustment.